PENGARUH DESAIN ATAU PENEMPATAN RUANG TUNGGU TERHADAP KENYAMANAN PASIEN DI LOKET PENDAFTARAN PUSKESMAS SURANADI - Sudiartha Hartawan, I Made Putu; Adam Hadi Suyanto (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
The Suranadi Health Center is one of the two youngest health centers in West Lombok district, this is the local government's response to its commitment to bringing health services closer to optimally improving health status, the operation of the Suranadi Health Center was inaugurated on January 29, 2018. The Suranadi Health Center is still relatively new. Therefore it is necessary to assess the spatial arrangement such as the design of the waiting room at the registration counter which can be a factor for patient comfort. This study aims to determine whether there is an effect of the design or placement of the waiting room on the comfort of the patient at the registration counter of the Suranadi Public Health Center. This research was analyzed by descriptive data analysis with a quantitative approach. The data collection technique for this study used observation. The population of this study were all patients from April to June and the sample in this study was 97 patients. Data collection techniques for this study used a questionnaire. Based on the results of the study using a sample of 97 patients, it was found that there was an influence of waiting room design/placement on patient comfort at the registration counter, 10 people who felt less comfortable were less comfortable with the placement design. Comfortable as many as 3 people (30.0 %), good amounting to 32 people, where who feel less comfortable as many as 4 people (12.5% ​​%), who feel comfortable as many as 28 people (88.7%), very good amounting to 55 people, where 5 people (9.1%) feel less comfortable, 50 people (90.9%) feel comfortable. This means that there is an effect of waiting room design / placement on patient comfort at the Suranadi Health Center in 2021.